2018
DOI: 10.1016/j.redox.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective mechanisms of DJ-1 against oxidative stress through modulating ERK1/2 and ASK1 signal transduction

Abstract: DJ-1 is a highly conserved multifunctional protein linked to both neurodegeneration and neoplasia. Among its various activities is an antioxidant property leading to cytoprotection under oxidative stress conditions. This is associated with the ability to modulate signal transduction events that determine how the cell regulates normal processes such as growth, senescence, apoptosis, and autophagy in order to adapt to environmental stimuli and stresses. Alterations in DJ-1 expression or function can disrupt home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 91 publications
4
55
0
Order By: Relevance
“…The ERK1/2 pathway is a classic mitogen-activated protein kinase signaling cascade that regulates cell proliferation and growth (34,35). In the present study, it was observed that silencing of AQP5 inhibited ERK1/2 signaling, consistent with the observations of prior studies (17,36).…”
Section: Discussionsupporting
confidence: 92%
“…The ERK1/2 pathway is a classic mitogen-activated protein kinase signaling cascade that regulates cell proliferation and growth (34,35). In the present study, it was observed that silencing of AQP5 inhibited ERK1/2 signaling, consistent with the observations of prior studies (17,36).…”
Section: Discussionsupporting
confidence: 92%
“…We found that 6-OHDA treatment of dopaminergic SH-SY5Y cells caused 3-fold increase in SNCA expression which is consistent with a previous research that shows 5′-UTR of SNCA is upregulated in response to cellular stress factors like MPP+, FeSO4 and 6-OHDA and increases α-synuclein expression in HEK-293T cells [5]. DJ-1 is known to play a role as an oxidative stress sensor, upregulates at first hours of oxidative stimuli and activates Elk1, an ETS domain containing transcription factor as a neuroprotection response [6]. To determine if Elk-1 overexpression is neuroprotective, we have cotransfected WT or A53T overexpressing cells with Elk1 and found that Elk1 expression together A53T mutant decreased cell viability (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the results about the suppression of ferroptosis were consist with MGO detoxification ability as DJ-1 ΔC3 and L187E mutants lost the inhibition of ferroptosis compared with DJ-1 WT. Besides, the suppression was more obvious in DJ-1 ΔC3 and L187E mutants than V51C mutant, indicating that the hydrophobic C terminus may have other effects such as involving regulation of signaling pathway [4, 6, 38]. All these data supported our previous discovery that DJ-1 was a negative modulator of ferroptosis providing new opportunities to facilitate ferroptosis-based cancer therapy [14].…”
Section: Discussionsupporting
confidence: 78%